Association of urinary metal levels with human semen quality: A cross-sectional study in China. (May 2016) - Wang, Yi-Xin; Sun, Yang; Feng, Wei; Wang, Peng; Yang, Pan; Li, Jin; Huang, Zhen; Chen, Ying-Jun; Liu, Chong; Sun, Li; Yue, Jing; Gu, Long-Jie; et al.
Abstract: Background: Exposure to metals, including essential and nonessential elements, has been linked to male reproductive health in animals. However, findings from human studies are inconsistent. Objective: To examine the associations between metal exposure at environmental levels and semen quality in a Chinese population by performing repeated measurements of urinary metals to estimate individual-level exposure. Methods: From March to June 2013, 1052 men seeking semen evaluation were recruited from the Reproductive Center of Tongji Hospital in Wuhan, China. Each man provided one semen sample and two urine sample. Semen quality parameters and urinary levels of 18 metals were determined. Associations between the urinary metal levels and semen quality parameters were assessed using confounder adjusted linear and logistic regressions. Restricted cubic spline analysis was performed to assess dose-response relationships between continuous metal measurements and outcomes. Results: Urinary levels of cadmium were significantly inversely associated with progressive sperm motility and total motility (both P < 0.02) based on multivariable linear regression models, consistent with the trends of increased odds ratios for below-reference semen quality parameters observed in the logistic models (both P < 0.05). Additionally, we found significant inverse associations of urinary molybdenum and lead with percentages of normal sperm morphology (both P < 0.05). These associations remained suggestive or significant after adjustment for multiple testing. They were also robust to the simultaneous consideration of multiple metals, and curves of restricted cubic spline showed clear dose-response relationships. Conclusion: Our findings suggest that environmental exposure to cadmium, molybdenum and lead may contribute to a decline in human semen quality. Highlights: We quantified 18 metals in 2104 urine samples from 1052 adult men. We examined the associations between urinary metals and semen quality parameters. Cadmium was inversely associated with progressive and total sperm motility. Molybdenum and lead were inversely associated with percent normal morphology.